The Diction used in the Novel on the Reader in a Novel "A Good Girl's Guide to Murder" by Holly Jackson - Balqis, Soraya; Auliya', Ummah Faradila; Mala Rohmana, Wahyu Indah (English Education, Linguistics, and Literature Journal, 2024)
Diction is the selection of the right words to form sentences that meet the requirements, have a harmonious meaning, and are successfully communicated to the listener so that language misunderstandings do not occur. Based on its meaning, diction in this research is separated into two categories: denotational meaning and connotative meaning. This research aims to describe the types of diction found in the novel A Good Girl's Guide to Murdered by Holly Jackson. In this research we used qualitative methods to obtain data, in this qualitative approach, we used a case study approach. The data collection technique in this method is by describing or investigating the subject or object. Descriptive methods are also used for research procedures or solving problems that are investigated by describing subjects or objects as well. Based on the results of the data analysis, there are two types of diction based on meaning. The novel also succeeded in making readers feel what was written in the novel. For this reason, the author has also succeeded in making readers enjoy the plot of the story while the most dominant meaning is that the research is widely used because it fits the context of the story in the novel.